DASP: a rosa na cruz do Estado Novo - Forgiarini, Giorgio (2021)
The empirical object of the research that gives rise to this thesis is the Administrative Department of the Public Service (DASP). The intention is to examine the organ from the theoretical references offered by two German thinkers, George W. F. Hegel and Max Weber, paying particular attention to their concepts of rationality and rationality of the State. The question to be answered is: What conceptions led to the creation of the DASP, as well as to the administrative reform of the 1930s? At first, we meddled in conceptual definitions, using the definitions of both Hegel and Weber about the theoretical framework. According to the first, Hegel, state rationality was based on the assumption that the State was endowed with a metaphysical power attributed to the Prince, whose materialization before society would take place through a body of legally invested employees. The Public Administration, then, would be an extension of the power of the Prince, endowed, even, with the same powers that endow royalty. Weber, on the other hand, analyzed the state through a liberal lens, comparing it to a private enterprise in a capitalist context. For him, the corps of State employees would act, not by investiture, but by contract, to act not only as an instrument of action for the Prince, but also as an obstacle to his impetus. According to Weber, State rationality has a name: Bureaucracy. In Brazil, the conceptions about the State and Public Administration have changed a lot since the discovery and the implantation of the hereditary captaincies, with the 1930s having seen one of the most radical morphoses in the Brazilian administrative apparatus. Driven by the obsession with rationalization, the Vargas regime began a profound process of administrative reforms, which gained momentum in 1938 with the creation of the Administrative Department of the Public Service (DASP), an administrative body immediately subordinate to the Presidency of the Republic with attributions that, over time, would exacerbate those of mere administrative advice. Customarily, Max Weber is credited with the founding doctrine of the Vargas administrative reform, as well as the creation of the DASP. However, this investigation shows that Weber did not influence Vargas' reformism, which we conceive based on three fundamentals, chronological, rhetorical and logical, duly addressed in the body of work. Furthermore, we could verify that the DASP was constituted under the strong influence of American theories, among which the theory of the Department of General Administration, by William Willoughby, with the objective of forming in Brazil a state apparatus in the Hegelian mold.